An empirical study on the semantics-pragmatics of two Romance confirmational tags - Elena Castroviejo; Laia Mayol (Isogloss)
This paper provides a fine-grained characterization of two confirmational tags in Catalan, oi? and eh?, starting with the novel claim that, despite appearances, they do not have the same distribution or meaning. While oi? is a rather unconstrained confirmational, eh? is proved to be sensitive to whether the main predicate of the sentence anchor p is objective or subjective. We ultimately propose that confirmational questions with oi? make a request for confirmation of the truth of the sentence anchor, whereas a confirmational with eh? is a request for the commitment of the addressee to the truth of the sentence anchor. Two consequences emerge from our analysis: oi? should be preferred when factual truths instead of opinions are conveyed, while eh? should be preferred in contexts where the speaker is not necessarily interested in finding out the truth of p. These predictions are tested in three experimental studies, which provide empirical support for the theoretical proposal regarding the different pragmatic contribution of both tags.